Performance Analysis of Various Interconnection Schemes of Solar Photovoltaic Array under Partial Shading Condition - Purohit, Jyoti; *, Naveen; Pareek, Smita (IJRDO - Journal of Electrical And Electronics Engineering, 2016)
Partial shading ruins the performance of solar photovoltaic systems by adversely affecting the insolation received by solar photovoltaic cells. Among several proposed techniques to reduce partial shading effect, one is to alter interconnections schemes. Several interconnections scheme have been reported in literature i.e. Series-parallel (SP), Bridge-linked (BL), Total-cross-tied (TCT), Honey-comb (HC) configuration etc. In this paper these interconnected schemes are investigated in order to suggest best topology for variousshade patterns. In addition the result of each configuration is also given in terms of characteristics curves.